Note on Onocleopsis hintonii (Onocleaceae), a new record for the state of Hidalgo, Mexico - Gómez-Noguez, Felipe; Mendoza-Ruiz, Aniceto; Pérez-García, Blanca (Instituto de Ecología, A.C., 2013)
Onocleopsis hintonii is reported for the first time for the state of Hidalgo, Mexico, adding the Onocleaceae Pic. Serm. family record. Data on their morphology and characteristics of their spores are presented.